2017
DOI: 10.1161/circgenetics.117.001839
|View full text |Cite
|
Sign up to set email alerts
|

Applying High-Resolution Variant Classification to Cardiac Arrhythmogenic Gene Testing in a Demographically Diverse Cohort of Sudden Unexplained Deaths

Abstract: High-resolution variant interpretation provides diagnostic accuracy and healthcare efficiency. Under-represented populations warrant greater inclusion in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
1
30
1
Order By: Relevance
“…This percentage is higher than even the demographic breakdown of the City of New York, with Black or African Americans making up 24.3% of the population ("United States Census Bureau", ). However, previous studies have shown that there is not an enrichment of P/LP variants in this population compared to others (Lin et al, ). The overrepresentation of the Black/African American population in our cohort may be due to an intrinsic factor not identified here, or the well‐documented barriers to care in minority populations (Espejo et al, ; Hayes, Riley, Radley, & McCarthy, ; Rositch, Atnafou, Krakow, & D'Souza, ).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…This percentage is higher than even the demographic breakdown of the City of New York, with Black or African Americans making up 24.3% of the population ("United States Census Bureau", ). However, previous studies have shown that there is not an enrichment of P/LP variants in this population compared to others (Lin et al, ). The overrepresentation of the Black/African American population in our cohort may be due to an intrinsic factor not identified here, or the well‐documented barriers to care in minority populations (Espejo et al, ; Hayes, Riley, Radley, & McCarthy, ; Rositch, Atnafou, Krakow, & D'Souza, ).…”
Section: Discussioncontrasting
confidence: 64%
“…The overrepresentation of the Black/African American population in our cohort may be due to an intrinsic factor not identified here, or the well‐documented barriers to care in minority populations (Espejo et al, ; Hayes, Riley, Radley, & McCarthy, ; Rositch, Atnafou, Krakow, & D'Souza, ). While this is not a novel discovery, as previous cohort study has elucidated such disparities (Lin et al, ), it is important to reiterate the point that people from underrepresented populations should be included in research.…”
Section: Discussionmentioning
confidence: 84%
“…The purpose of these studies was to functionally examine HCN4 VUS identified in our previous work, where we performed variant classification using genetic screening of a cardiac arrhythmogenic testing panel of ∼300 cases of sudden unexplained deaths . In the latter study, we have identified four HCN4 VUS and one likely benign (LB) variant.…”
Section: Resultsmentioning
confidence: 99%
“…With the power of massively parallel sequencing, testing a large number of cardiac disease‐associated genes simultaneously has become feasible. There are now several reports of postmortem testing to identify pathogenic variants directly linked to an underlying heritable cardiac disease; hence, the potential for fatal arrhythmia and sudden death . When there is insufficient evidence to classify variants as either benign or pathogenic, they are considered variants of uncertain significance (VUS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation